Thomas Ashe : (Leader of the North County Dublin Volunteers in the Rising) - Keogh Brothers Ltd.; Powell Press, Dublin (Dublin : Powell Press, 22 Parliament St., 1910)
Half length, facing left portrait of Thomas Ashe wearing a suit and tie, printed on a postcard.
Title inscribed below image includes "Sentenced to Death; Sentence commmuted to Penal Servitude for Life.".
Inscribed above image "Irish Rebellion, May 1916".
catalogued
Keywords: Ashe, Thomas, -- 1885-1917; Irish Volunteers; Revolutionaries -- Ireland -- 1910-1920; Ireland -- History -- Easter Rising, 1916; Postcards -- Irish -- 1910-1920; Portrait prints -- Irish -- 1910-1930